The Effectiveness of Educational Game-Based Learning on Elementary School Student Learning Motivation - Kadek Hengki Primayana; Made Mita Citra Dewi; Luh Put Diska Ryanti; Ketut Ayu Anindya Dewi; Ketut Gea Putra Dhinata; Kadek Cintia Paramita (Indonesian Journal Publisher, 2026)
Technological developments have significantly impacted the world of education, particularly in the use of more interactive and engaging learning media. However, elementary school students' learning motivation remains relatively low due to the monotonous and teacher-centered learning process. This article aims to examine the effectiveness of educational game-based learning on elementary school students' learning motivation. This research employed a literature review method by analyzing 25 scientific articles published between 2000 and 2025 related to educational games and student learning motivation. The articles were collected from Google Scholar, Scopus, and national journal databases. The results of the study indicate that educational game-based learning can increase student learning motivation by creating a fun, interactive, and engaging learning environment. The use of educational games also helps improve student activity, concentration, learning interest, and learning outcomes. Furthermore, educational games align with the characteristics of elementary school students, who are more interested in visual and interactive learning. Thus, educational game-based learning can be an effective solution to increase elementary school students' learning motivation and help teachers create a more creative and innovative learning process. This study contributes by providing a comprehensive synthesis of previous research findings regarding the effectiveness of educational game-based learning in improving elementary school student’s learning motivation.